Mixed–phase α/β–AgAl0.4Ga0.6O2 solid solution with heterojunction for enhanced visible–light photocatalytic activity. (November 2017) - Zhang, Maocai; Dang, Lingyan; Tian, Chen; Zhao, Shifeng; Lu, Qingshan
Abstract: Mixed–phase α/β–AgAl0.4 Ga0.6 O2 solid solution with heterojunction was fabricated through phase transformation. The samples with high crystallinity showed the mixed morphology of near–spherical shape of β phase and the platelet of α phase. The UV–vis absorption edges ranged from 460 to 520 nm by controlling the ratio of two phases. It was found that the mixed–phase α/β–AgAl0.4 Ga0.6 O2 with the weight percentage of 36% for α–AgAl0.4 Ga0.6 O2 showed the highest photocatalytic activity. This might be attributed to the absorption behavior for efficiently utilizing visible light and the phase heterojunction for promoting the separation of photogenerated carriers. The survey of photocatalytic mechanism indicated that reactive h + and O2 − were the oxygen active species. In addition, a possible transfer process of charge carriers in photocatalysis was proposed. This work demonstrates that the design of mixed–phase heterojunction is an efficient approach to enhance photocatalytic activity. Graphical abstract: Highlights: Mixed–phase α/β–AgAl0.4 Ga0.6 O2 with heterojunction prepared by hydrothermal method. The weight percentage of two phases controlled by the reaction time. The visible–light absorption behavior related to the weight percentage of two phases. Enhanced photocatalytic performance attributed to the absorption behavior and heterojunction.